VITAMIN B1PROMOTED GREEN SYNTHESIS OF BENZOFURAN CHALCONES: PROMISING SCAFFOLDS FOR DRUG DEVELOPMENT IN ANTIMICROBIAL - VENKAT S., SURYAWANSHI (Innovare Journal of Sciences, 2020)
Objective: To develop metal free and environmentally benign synthetic method for the synthesis of chalcones bearing benzofuran scaffolds. Materials and Methods:Starting material chloroacetone,anhydrous potassium carbonate, different aromatic aldehydes, ethanol and vitamin B1 of AR grade wereused for synthesis.Various chalcones were synthesized byClaisen-Schmidt condensation.The structure of the synthesized compounds was confirmed by elemental analysis, IR,1H NMR and mass spectra. Results:In this context we have tried new metal free and environmentally benign synthetic method for synthesis of the pharmaceutically important molecule 1-(4-substituted-1-benzofuran-2-yl) substituted chalcones and its derivatives and it was screened for their antimicrobial activity.Most of the compounds exhibited the good to moderate activity. Conclusion:Herein we have tried a highly efficient protocol for the synthesis of chalconesa good result with variety of functionalities, a high yield of products, and the recoverability of this catalyst.Vitamin B1 as a catalyst has been developed using green solvent EtOH.